2006
DOI: 10.1111/j.1471-0374.2006.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Transnational involvement and social integration

Abstract: In this article we offer a quantitative examination of the extent to which migrants from various countries are involved in transnational activities and have transnational identifications. The study is based on a survey of 300 immigrants (from the USA, Japan, Iraq, former‐Yugoslavia, Morocco and the Dutch Antilles) living in the Netherlands. The respondents are deliberately chosen to include different categories of immigrants. Transnational activities constitute a substantial part of their lives and are to a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
272
3
16

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(300 citation statements)
references
References 16 publications
9
272
3
16
Order By: Relevance
“…Guarnizo, Portes, and Haller (2003) found that increased education of immigrants increases political participation in receiving and origin countries. Snel, Engbersen, and Leerkes (2006) countered the idea that immigrant groups (Moroccans, Antilleans) who are often said to be poorly integrated into Dutch society necessarily show more transnational involvement. In a similar vein, the literature on migrant remittances has questioned the hypothesis that remittances automatically decline over time due to progressive integration and weakening ties (Brown 1994;de Haas and Plug 2006;Taylor 1999;van Dalen, Groenewold, and Fokkema 2005).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Guarnizo, Portes, and Haller (2003) found that increased education of immigrants increases political participation in receiving and origin countries. Snel, Engbersen, and Leerkes (2006) countered the idea that immigrant groups (Moroccans, Antilleans) who are often said to be poorly integrated into Dutch society necessarily show more transnational involvement. In a similar vein, the literature on migrant remittances has questioned the hypothesis that remittances automatically decline over time due to progressive integration and weakening ties (Brown 1994;de Haas and Plug 2006;Taylor 1999;van Dalen, Groenewold, and Fokkema 2005).…”
Section: Introductionmentioning
confidence: 97%
“…At first glance, this pattern seems to reflect the collective experience of "guest workers" in Europe mentioned above, who often ended up staying while experiencing high unemployment and social marginalization. Their prolonged stay and settlement did not, however, lead to a significant decrease in the transnational ties they maintained with origin societies (de Bree 2007;Reniers 2001;Snel, Engbersen, and Leerkes 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have pointed out that there are a multitude of terms (Vertovec 1999 (Vertovec 1999), transnational spaces (Faist 2000), transnational social fields (Basch et al 1994), global 'oecumene' (Hannerz 1996), transnationalism (Portes et al 1999), and transnational involvement (Snel et al 2006). These terms are used interchangeably with 'transnational networks' and 'cross border activities' and are generally used loosely.…”
Section: Concepts and Issuesmentioning
confidence: 99%
“…Guarnizo, Portes, and Haller 2003); and still others examine personal ties and contacts (e.g. Mau and Mewes 2008;Mau 2010;Snel, Engbersen, and Leerkes 2006). Since people are involved in different transnational dimensionseconomic, political, cultural, familial -to different degrees (see Levitt 2003), the relationship with social inequalities is also likely to vary across these dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Portes, Guarnizo, and Haller 2002;Waldinger 2008) and from Europe (e.g. Snel, Engbersen, and Leerkes 2006;Schunck 2011;Mau and Mewes 2008). However, they are mostly concerned with the social integration of migrants and often include only few aspects relevant to social inequalities.…”
Section: Introductionmentioning
confidence: 99%